One-way flow system for improvement of the acid sulfate soil reclamation process in the Belanti II tidal swamp irrigation network, Central Kalimantan, Indonesia. - Setiawan, A.; Wignyosukarto, B. S.; Rahardjo, A. P. (2022)
Belanti II tidal irrigation network was developed in 1980 on acid sulphate soil with an area of approximately 3976 ha. Belanti II has one primary channel and several secondary channels, without any water structures that regulate the direction of flow. Two-way flow occurs in the channel, supplying fresh water from the river at high tide and flowing back into the river at low tide. This two-way flow system inhibits the leaching process of acid sulphate soil. Up to now, acid sulfate soils are still found at a depth of 50-75 cm with a pH of 2.5 ∼ 3.5. A one-way flow system is expected to improve water circulation, assisted by channel rehabilitation, collector channels and water control structures. The spillway structure at the secondary channel regulates the freshwater supply at high tide and the flap gate at the end regulates the flow of water to the collector channel at low tide. Hydraulic analysis was carried out using HEC-RAS modelling. The results showed the ability of the system to supply fresh water, flushing/leaching acid sulfate water and drainage the toxic water. The effectiveness of the system is evaluated regarding the direction and the volume of freshwater flowing into the secondary channel. © Published under licence by IOP Publishing Ltd.